2014
DOI: 10.1590/bjpt-rbf.2014.0056
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between static postural control and the level of functional abilities in children with cerebral palsy

Abstract: Background: Postural control deficits can impair functional performance in children with cerebral palsy (CP) in daily living activities. Objective: To verify the relationship between standing static postural control and the functional ability level in children with CP. Method: The postural control of 10 children with CP (gross motor function levels I and II) was evaluated during static standing on a force platform for 30 seconds. The analyzed variables were the anteroposterior (AP) and mediolateral (ML) displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
1
22
0
4
Order By: Relevance
“…We acknowledge that our findings were interpreted in light of the assumption that a decrease in the computed COP variables due to the application of SR indicated balance improvements. In agreement, prior studies on postural balance in CP indicated that decreased COP sway is associated with increased stability [ 7 , 9 , 26 , 68 ]. Specifically, and similar to our COP outcome measures in the no stimulation condition between the 2 groups, children with CP usually demonstrate increased postural sway during quiet stance compared to their TD peers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We acknowledge that our findings were interpreted in light of the assumption that a decrease in the computed COP variables due to the application of SR indicated balance improvements. In agreement, prior studies on postural balance in CP indicated that decreased COP sway is associated with increased stability [ 7 , 9 , 26 , 68 ]. Specifically, and similar to our COP outcome measures in the no stimulation condition between the 2 groups, children with CP usually demonstrate increased postural sway during quiet stance compared to their TD peers.…”
Section: Discussionsupporting
confidence: 89%
“…The development of movement and posture in CP is primarily affected by a static lesion that occurs in the developing fetal or infant brain [ 5 ]. Although the brain injury is not progressive, it results in motor and functional impairments that are progressive through a lifetime and related with reduced ambulatory ability [ 6 ] and poor balance performance [ 7 – 9 ]. In particular, postural instability has the most significant contribution to the model of primary impairments (i.e., related to the brain injury) compared to the muscle tone and motor coordination deficits in this population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, such a therapeutic intervention will improve their functional level. Postural control deficit is one of the main causes of gait disorders among children with cerebral palsy (Pavão et al, 2014;Stackhouse et al, 2007). Provision of an intervention consisting of task -oriented training to these children improved their balance and walking ability (Peungsuwan et al, 2017).…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Postural control is defined as ensuring proper posi-tioning of the body in space as well as maintaining body alignment and stability by controlling the center of gravity in the base of support (5). Dysfunction in postural control is a key problem in children with CP.…”
Section: Introductionmentioning
confidence: 99%